Kecerdasaan emosional: Kunci sukses dalam akademik dan kehidupan sosial - Utami, Lukas Sri (Maliki Interdisciplinary Journal, 2024)
Emotional intelligence (EI) is a key factor in achieving success in both academic and social settings. In the academic world, EI helps students manage stress, improve communication and build positive relationships. In social life, EI enables individuals to understand and respond to others’ emotions with empathy, maintain harmonious interpersonal relationships, and manage conflict more effectively. However, EI development faces challenges such as lack of awareness, limited resources, difficult evaluation, curriculum integration, and resistance to change. Overcoming these challenges requires collaborative efforts from educators, policymakers and communities to raise awareness, provide training and develop accurate evaluation methods. By integrating EI more structurally, can create a supportive academic environment and a more empathic society, providing long-term benefits to individuals’ emotional well-being and social success.